Mastering graphics programming with Vulkan : develop a modern rendering engine from first principles to state-of-the-art techniques /: develop a modern rendering engine from first principles to state-of-the-art techniques. (2023) - Castorina, Marco; Sassone, Gabriel
No abstract available